Awareness, knowledge and belief regarding bitter leaf use: A cross-sectional study in Nigeria - Obi Peter Adigwe; Godspower Onavbavba; Ofure Omoarelojie (PLoS ONE, 2025)
Background Vernonia amygdalina, also known as bitter leaf, is a plant that is widespread in Nigeria. Bitter leaf plant has several medicinal properties, and the plant is also widely used due to its various gastronomic applications. This study aimed to assess awareness, knowledge, and beliefs regarding bitter leaf use. Methods A cross-sectional study was undertaken in Nigeria. Paper-based questionnaires were administered to participants, and the data were analysed using Statistical Package for Social Sciences. Results Of the 500 questionnaires that were administered, a total of 401 copies were completed and returned, resulting in a response rate of 80.2%. About two-thirds (65%) of the study participants were females, whilst 35% were males. Almost all the participants (98%) had heard about bitter leaf, the total mean score for knowledge of bitter leaf use amongst the respondents was 4.80 ± 2.14 (Range 0–9). Using the Bloom cut off, only about 11.7% of the population had good knowledge and 27.2% had moderate knowledge regarding bitter leaf. However, more than three-quarters of the sample (79.6%) linked bitter leaf to its glucose lowering properties, towards optimal maintenance of blood sugar levels. The respondents’ sources of information on bitter leaf use were mainly from relatives (88%) and social media (19.9%). Statistically significant findings revealed stronger belief amongst females regarding the employment of bitter leaf as a weight loss intervention (p = 0.042). Conclusion Although most participants were familiar with the bitter leaf plant, only a few of them had adequate knowledge of its properties. Given its widespread use, a comprehensive understanding is imperative to prevent misuse. Findings from this study indicate that most people rely on informal sources for information about the plant, potentially leading to misconceptions regarding proper use. Consequently, evidence-based public education is needed to promote safe consumption and fully harness the plant’s nutritional and medicinal benefits.